CAPITAL AND MARKET: BAGAIMANA MENINGKATKAN PRODUKSI “BIHUN KUNTUL” - Edrick Gian Gunawan; Liliana Dewi (Politeknik Ubaya, 2021)
Vermicelli is a type of food originating from China, vermicelli are white noodles made from processed rice flour. Kuntul vermicelli is a rice vermicelli produced by company Gizi Pangan Nusantara. There is an increasing demand for vermicelli but the production quantity is difficult to increase, this problem can be caused by several factors, therefore the researcher will explore the factors that can affect the production of Kuntul vermicelli. The purpose of this study is to determine the factors that can affect Kuntul vermicelli production to increase the quantity of Kuntul vermicelli that can be produced. Respondents in this study are vermicelli companies registered on the website of the ministry of industry. The number of samples used was 50 respondents. The research approach was carried out quantitatively by using exploratory factor analysis method. The data collection method used a questionnaire based on 4 variables which are thought to be factors that influence the production of Kuntul vermicelli. The results of this study indicate that there are 2 factors that are formed, namely factor 1 consists of personal capital and the amount of market demand while factor 2 consists of business condition after adding capital and raw material inventory.